Racially minoritised workers’ incivility experiences, and consequences within maternity settings: a multimethod longitudinal qualitative exploration - Olivia Joseph; Ghazala Mir; Beth Fylan; Rebecca Lawton (International Journal for Equity in Health, 2026)
Abstract Background Workplace incivility is a global concern in healthcare, undermining staff wellbeing, organisational functioning and patient safety. In England, despite National Health Service (NHS) commitments to equality and inclusion, racially minoritised staff continue to experience inequities shaped by racism and organisational culture. How these dynamics influence incivility and its safety consequences for staff and patients’ remains underexplored. Methods and results This study presents a longitudinal qualitative critical ethnography across two NHS maternity settings. Sixteen in-depth interviews and eleven eight-week WhatsApp diaries were conducted with racially minoritised midwives, administrative and support roles. Additionally, relevant documents were examined in parallel, including policies, standard operating procedures and reports identified by informants. By applying the theory of racialised organisations and an inductive analysis, findings revealed two key manifestations of incivility. First, embedded in routine work processes, such as inequitable work allocation, hostile documentation practices and inadequate support. Second, within informal social interactions, including negative stereotyping of racially minoritised colleagues and patients, and exclusionary practices. Reported examples of incivility highlighted compromised care through treatment delays and the safety risks of emotionally depleted staff, silenced concerns, eroded team functioning and reduced psychological safety. Findings showed how structural inequities and racialisation shape everyday incivility across different roles. Informants reported weak organisational learning and strained cultures contributed to incivility experiences, exacerbated by resource depletion and entrenched racialised dynamics. Conclusions Despite regulatory emphasis on speaking up, mistrust, fear and silencing persisted amid ongoing inequitable treatment. Improving safety and equity in maternity care, requires multilevel effort to strengthen antiracism leadership, better support racialised staff and address racialised incivility to improve team dynamics and patient safety.